BMP-7/Smads-induced inhibitor of differentiation 2 (Id2) upregulation and Id2/Twist interaction was involved in attenuating diabetic renal tubulointerstitial fibrosis. (November 2019) - Xiao, Ying; Jiang, Xiaohan; Peng, Can; Zhang, Yingying; Xiao, Yawen; Liang, Dan; Shi, Mingjun; Wang, Yuanyuan; Zhang, Fan; Guo, Bing
Abstract: Renal tubular epithelial–mesenchymal transition (EMT) is the main pathological change in diabetic renal tubulointerstitial fibrosis. Mounting evidence indicates that the inhibitor of differentiation 2 (Id2) protein acts as a negative regulatory factor in organ fibrosis and can inhibit or reverse the process of fibrosis. However, its specific regulatory mechanism is not clear. Diabetes mellitus (DM) rat models were established by injecting rats with streptozotocin and sacrificing them after 16 weeks. Rat renal tubular epithelial cells (NRK-52E) were cultured with normal and high glucose. Immunohistochemical analysis, double immunofluorescence staining, co-immunoprecipitation, Western blot analysis, and real-time polymerase chain reaction were used to determine the expression of Id2, Twist, Smad1/5/8, E-cadherin, α-smooth muscle actin (α-SMA), and collagen Ⅳ. The results showed that bone morphogenetic protein-7 (BMP-7) upregulated the expression of Id2 against high-glucose-induced EMT and extracellular matrix secretion. Moreover, only the simultaneous knockdown of Smad1, Smad5, and Smad8 downregulated the expression of Id2, which was not altered by the individual knockdown of Smad1, Smad5, and Smad8. Basic helix-loop-helix (bHLH) transcription factors were essential for Id2 to regulate the role of downstream target genes, and Twist was a bHLH transcription factor. Therefore, the expression of Twist was examined in this study. Twist was found to be highly expressed in the kidney of DM rats and renal tubular epithelial cells cultured with high glucose. The overexpression of Id2 did not alter the expression of Twist, but the interaction between Id2 and Twist was enhanced. In conclusion, the data showed the specific mechanism underlying Id2 negative regulation in diabetic renal tubulointerstitial fibrosis.